2021
DOI: 10.1371/journal.pone.0242641
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Abbott ARCHITECT HIV Ag/Ab combo assay for determining recent HIV-1 infection

Abstract: Background Given the challenges and costs associated with implementing HIV-1 incidence assay testing, there is great interest in evaluating the use of commercial HIV diagnostic tests for determining recent HIV infection. A diagnostic test with the capability of providing reliable data for the determination of recent HIV infection without substantial modifications to the test protocol would have a significant impact on HIV surveillance. The Abbott ARCHITECT HIV Ag/Ab Combo Assay is an antigen/antibody immunoass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Although we currently lack ideal methods for estimating changes in HIV incidence in response to decreases in diagnosis delay, objective measures of recency will be key moving forward. Objective measures of recency include recency assays [28–32], identification of Stage 0 HIV infection (new diagnosis with a negative HIV test in the prior 6 months prior), and identification of acute HIV infection (antigen positive/antibody negative) [33]. First, as suggested by Song et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although we currently lack ideal methods for estimating changes in HIV incidence in response to decreases in diagnosis delay, objective measures of recency will be key moving forward. Objective measures of recency include recency assays [28–32], identification of Stage 0 HIV infection (new diagnosis with a negative HIV test in the prior 6 months prior), and identification of acute HIV infection (antigen positive/antibody negative) [33]. First, as suggested by Song et al .…”
Section: Discussionmentioning
confidence: 99%
“…Use of testing history alone could be a pragmatic approach to correct for seroconversion in countries lacking detailed clinical or serological information. Where collected, information from diagnostic tests could also provide a useful proxy for recency, as recent studies have shown correlation between a 'recent' limiting antigen result and a signal-tocut-off ratio <250 in the widely-used Abbott Architect Ag/Ab assay [45,46].…”
Section: Discussionmentioning
confidence: 99%
“…64 The approved intended use of this test is as a qualitative aid to diagnosis of HIV infection; however, the quantitative information contained in the signal to cutoff ratio has been used in research to discriminate recent from long-term infections. [64][65][66] Because this test relies in part on anti-HIV antibody levels, it is also subject to false classification of infection as recent when viral replication is suppressed and should be used in combination with VL tests in a RITA to reduce the FRR. Relatively less is known about the optimal threshold to use when implementing a RITA using ARCHITECT, compared to the LAg assay.…”
Section: Types Of Recency Testsmentioning
confidence: 99%